A functional variant of the long noncoding RNA AL110200 is associated with the risk of ischaemic stroke recurrence. (1st June 2021) - Song, Li; Li, Hao; Suo, Miaomiao; Sun, Yingying; Su, Ming; Song, Yan; Xiao, Ning; Hui, Rutai; Qin, Chunchang; Chen, Jingzhou
Abstract: Background and purpose: This study aimed to test the hypothesis that long noncoding RNA (lncRNA) AL110200 exerts a proinflammatory effect on atherosclerosis and that the variant rs901681 contributes to ischaemic stroke incidence and recurrence. Methods: The expression of AL110200 was analyzed in THP‐1 cells treated with oxidized low‐density lipoprotein and in human peripheral blood in a coronary heart disease and control population to determine the role of AL110200 in atherosclerosis. The effect of AL110200 on cell adhesion and invasion was tested. The plasma level of leukotriene B4 and rs901681 genotype distribution were assessed in 220 participants. In 1004 ischaemic stroke patients and 1434 controls, the association between rs901681 and stroke incidence was analyzed by logistic regression, and the association of rs901681 and stroke prognosis was analyzed using Kaplan–Meier analysis and the Cox proportional hazards model. Results: Increased expression of AL110200 was observed in THP‐1 cells under oxidized low‐density lipoprotein treatment. Knockdown of AL110200 reduced the adhesive and invasive ability of THP‐1 cells. AL110200 expression in peripheral blood was significantly higher in the coronary heart disease group than in the controls. The GG genotype of rs901681 is associated with reduced plasma leukotriene B4. In the ischaemic stroke population, rs901681 was not associated with ischaemic stroke incidence ( p  = 0.686). Patients carrying rs901681 GG had a lower risk for stroke recurrence at age ≥60 years ( p  = 0.001), cardiovascular stroke death ( p  = 0.022) and all‐cause mortality ( p  = 0.034) in the all‐age group. Conclusions: AL110200 might exert a proinflammatory effect on atherosclerosis, and the variant rs901681 might be a strong predictor of stroke prognosis in ischaemic stroke patients. Abstract : LncRNA AL110200 may mediate the inflammation associated with atherosclerosis by regulating the adhesion and invasion of monocytes. The highly evolutionarily conserved variant rs901681 GG genotype may be associated with the regulation of LTB4 expression levels and thereby affect atherosclerosis. The prospective analysis revealed that the rs901681 GG genotype notably decreased the risk of stroke recurrence in patients aged ≥60 years and Csdeath and all‐cause mortality in all‐age.